ANALYSIS OF IMPROVING DIGITAL IMAGE QUALITY USING ARITHMETIC MEAN FILTER ALGORITHM - Mamed Rofendi; Kristian Siregar (INFOKUM, 2019)
Image is a combination of points, lines, fields, and colors to create an imitation of a physical or human object. Digital imagery consists of square elements called pixels. An example of an image is an image. However, sometimes the image can also experience a decrease in quality (degradation). Images or pixels that have decreased image quality in image processing are called noise. This research discusses the enhancement of digital image quality using the Median filter technique to reduce noise. In this study using color image data (RGB) as test data and then converted into grayscale images to determine the gray degree of the image. The Grayscale image is stored in the database. Then noise is generated by using random numbers. The type of noise used is Salt & Pepper. Noise salt & pepper is a type of noise that has a value of 0 and 255 spread. To reduce noise salt & Pepper, an Arithmetic Mean Filter method or technique is used.